Analisis Value Engineering untuk Penghematan Biaya Pekerjaan Arsitektur pada Proyek Apartemen X Tangerang Selatan - Ramadhan, Muhammad Mahesa; Kurniasari, Marisa Wahyu (Universitas Kristen Maranatha, 2024)
The demand for housing among the population is substantial, leading to the challenge of insufficient land area for construction. We construct residential developments horizontally to address this issue. However, the construction costs associated with this approach are significantly higher. As a result, there is a need for various efforts to optimize construction costs, and one such initiative involves the application of value engineering methods. The X Apartment Project in South Tangerang, with a construction value of Rp. 203,204,569,971, is the focus of this study. Based on the significant value of the development, this study seeks to estimate cost savings through value engineering analysis, particularly in the area of architectural work. This research method has four stages, namely the information stage, the speculation stage, the analysis stage, and the presentation stage. The observations lasted one month and were conducted using a questionnaire instrument. The Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method provides an alternative decision-making system. This study demonstrates that the application of value engineering reduced the initial cost of Rp. 203,204,569,971 to Rp. 201,685,400,449, with a reduction of 0.75% in window work (J1), glass door work (PL1), door work (PD1), light brick wall work, and homogenous tile KR2B floor tile work.